High throughput single cell long-read sequencing analyses of same-cell genotypes and phenotypes in human tumors - Shiau, Cheng-Kai; Lu, Lina; Kieser, Rachel; Fukumura, Kazutaka; Pan, Timothy; Lin, Hsiao-Yun; Yang, Jie; Tong, Eric L.; Lee, GaHyun; Yan, Yuanqing; Huse, Jason T.; Gao, Ruli (Nature communications, 2023)
Single-cell nanopore sequencing of full-length mRNAs transforms single-cell multi-omics studies. However, challenges include high sequencing errors and dependence on short-reads and/or barcode whitelists. To address these, we develop scNanoGPS to calculate same-cell genotypes (mutations) and phenotypes (gene/isoform expressions) without short-read nor whitelist guidance. We apply scNanoGPS onto 23,587 long-read transcriptomes from 4 tumors and 2 cell-lines. Standalone, scNanoGPS deconvolutes error-prone long-reads into single-cells and single-molecules, and simultaneously accesses both phenotypes and genotypes of individual cells. Our analyses reveal that tumor and stroma/immune cells express distinct combination of isoforms (DCIs). In a kidney tumor, we identify 924 DCI genes involved in cell-type-specific functions such as PDE10A in tumor cells and CCL3 in lymphocytes. Transcriptome-wide mutation analyses identify many cell-type-specific mutations including VEGFA mutations in tumor cells and HLA-A mutations in immune cells, highlighting the critical roles of different mutant populations in tumors. Together, scNanoGPS facilitates applications of single-cell long-read sequencing technologies. There is a need for methods that allow the analysis of single-cell long-read sequencing data without depending on known barcode lists or short-read sequencing. Here, the authors develop scNanoGPS, a tool that can independently deconvolute long reads into single cells and single molecules, and apply it on tumour and cell line data.